2009
DOI: 10.3310/hta13230
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic strategies using DNA testing for hereditary haemochromatosis in at-risk populations: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 266 publications
(133 reference statements)
1
11
0
Order By: Relevance
“…Despite the difficulties in synthesizing the evidence and drawing conclusions from studies that employed diverse methods and reported results in different ways, common (Bryant et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Despite the difficulties in synthesizing the evidence and drawing conclusions from studies that employed diverse methods and reported results in different ways, common (Bryant et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Additional studies were sought by searching bibliographies of related publications and through contact with experts. Search strategies are available on request, and further details are available elsewhere (Bryant et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations